(untitled) (Jurnal Arsitektur ARCADE, 2026)
Most studies on restaurant customer satisfaction focus on food quality, service quality, price, and ambience, while research examining spatial layout characteristics remains limited. In all you can eat (AYCE) restaurants, customers actively move between dining and food service areas, making spatial layout an important factor in shaping user experience. This study aims to identify spatial layout characteristics that support customer satisfaction in AYCE restaurants. A descriptive quantitative approach was employed involving 234 respondents who had previously visited AYCE restaurants. Data were collected through questionnaires and analyzed using rating scale and spatial analysis across three restaurant layout types based on spatial relationships, circulation patterns, spatial arrangement, and accessibility. The findings indicate that layouts receiving the highest evaluations are characterized by clear spatial relationships, easy to follow circulation paths, organized zoning, convenient access to key facilities, and low movement conflicts. The results suggest that customer satisfaction tends to be higher in spatial configurations that simultaneously support user orientation, smooth movement, and easy access. These findings may serve as a reference for designing AYCE restaurant layouts that are more responsive to user needs.